DeskJockey: Exploiting Passive Surfaces to Display Peripheral Information - Kellar, Melanie; Inkpen, Kori (11th IFIP TC13 Conference in Human-Computer Interaction (INTERACT 2007), 2007)
This paper describes DeskJockey, a system to provide users with additional display space by projecting information on passive physical surfaces in the environment. The current DeskJockey prototype utilizes a projected desk and allows information to be moved easily between active and passive displays using a world-in-miniature interaction metaphor. A four-week, in-situ field study was conducted to compare usage of DeskJockey with typical multiple monitor use. The results revealed potential for utilizing passive physical surfaces in this manner and demonstrated that this type of display space has distinctive affordances and benefits which enhance traditional display space.